Unusual presentation of leptospirosis in the late stage of pregnancy - Gaspari, R; Annetta, M G; Cavaliere, F; Pallavicini, F; Grillo, R; Conti, G; Antonelli, M; Tafani, C; Proietti, R (Minerva anestesiologica, 2007)
Here we report a case of leptospirosis without fever during the late stage of pregnancy in which the initial clinical presentation was more suggestive of a pregnancy-related liver dysfunction rather than an infectious disease. A 32-year-old primipara at 37 week of gestation was hospitalised with a 10-day history of nausea, vomiting, and abdominal pain without fever. Initial routine blood tests showed hyperbilirubinemia, a moderate increase in transaminase levels, severe coagulopathy and an increased creatinine level. On clinical suspicion of pregnancy-related liver dysfunction such as HELLP syndrome (hemolysis, elevated liver enzyme levels, low platelet count) or acute fatty liver of pregnancy (AFLP), emergency caesarean section was performed and a healthy baby was delivered. Postoperatively, the patient was stable, but 5 days later she developed clouding of consciousness, severe jaundice and respiratory failure. At this time, an infectious disease was considered and leptospirosis was confirmed by serological tests. In conjunction with intensive care management, antibiotic therapy was given; the patient was discharged in good condition and her baby did not develop signs of active leptospirosis. While leptospirosis is rare in pregnancy, this is the first report of acute infection without fever mimicking the clinical pattern of HELLP syndrome or AFLP